A new organic carbon detector for size exclusion chromatography. - Allpike, Bradley; Heitz, Anna; Joll, Cynthia; Kagi, Robert (Elsevier, 2007)
A novel organic carbon detector (OCD) for size exclusion chromatography (SEC), and its application to the characterisation of aquatic natural organic matter (NOM) in natural and treated potable water samples, is described. The instrument uses a conventional UV-persulfate oxidation technique to convert organic carbon to CO2. The novelty of the technique is detection of the evolved CO2 using a sensitive Fourier transform infrared (FTIR) spectroscopy 'lightpipe' detector originally designed for detection of analytes after gas chromatographic separation. With the exception of the lightpipe, the OCD system was constructed using simple, inexpensive, readily available components. The system was designed to minimise deadvolume, allowing for use of smaller sample sizes and smaller columns, substantially shortening analysis time, while maintaining chromatographic integrity through the OCD system. Downscaling resulted in some loss of separation but it was shown that this was caused by thelower separation efficiency of the smaller capacity column, rather than from sample dispersion within the OCD system.